2015
DOI: 10.1016/j.combustflame.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

A combined computational and experimental characterization of lean premixed turbulent low swirl laboratory flames II. Hydrogen flames

Abstract: a b s t r a c tWe present simulations of laboratory-scale Low Swirl Burner (LSB) flames in order to develop a characterization of the interaction of thermal/diffusive unstable flames with turbulence at the correct scales of laboratory experiments. A Lagrangian diagnostic was developed to overcome the pitfalls of traditional Eulerian analysis techniques when applied to cellular flame systems, including the lack of a well-defined measure of ''flame progress'' and the time-dependent strain and curvature fields th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Recent studies also investigate the dependence of S T on the low temperature fuel chemistry (Won et al 2014), high pressure (Bradley et al 2013; quantified variations of the vorticity and strain rate of fluid parcels undergoing combustion by tracking Lagrangian fluid particles and using the three-dimensional, timeresolved experimental measurement in premixed dimethyl-ether/air piloted jet flames. Day et al (2015) observed the complex nature of thermodynamic and chemical evolutions along Lagrangian trajectories, including the non-monotonic evolution of temperature within fluid parcels, in a joint experimental and computational study of lean hydrogen turbulent premixed flames in low swirl burners. Hamlington et al (2017) examined the effects of high-speed turbulence on the non-monotonic thermochemical trajectories in DNS of hydrogen-air premixed flames.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also investigate the dependence of S T on the low temperature fuel chemistry (Won et al 2014), high pressure (Bradley et al 2013; quantified variations of the vorticity and strain rate of fluid parcels undergoing combustion by tracking Lagrangian fluid particles and using the three-dimensional, timeresolved experimental measurement in premixed dimethyl-ether/air piloted jet flames. Day et al (2015) observed the complex nature of thermodynamic and chemical evolutions along Lagrangian trajectories, including the non-monotonic evolution of temperature within fluid parcels, in a joint experimental and computational study of lean hydrogen turbulent premixed flames in low swirl burners. Hamlington et al (2017) examined the effects of high-speed turbulence on the non-monotonic thermochemical trajectories in DNS of hydrogen-air premixed flames.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the leading research groups succeeded already in 3D DNSs of highly turbulent premixed flames by allowing for density variations and complex combustion chemistry [4][5][6][7][8][9][10]. Moreover, DNS of laboratory flames were also performed [11,12]. However, while advancement to simulations of increasingly challenging problems was in the focus of the numerical combustion community over the past decade, unique opportunities offered by DNS for scrutinizing foundations of turbulent combustion models did not seem to be exploited in full measure.…”
Section: Introductionmentioning
confidence: 99%
“…The selected equivalence ratio of φ = 0.4 is characteristic of conditions investigated in low swirl burners [47,48]. Before presenting the two-and three-dimensional simulations, a one-dimensional analysis of this configuration is discussed in the following section.…”
Section: Premixed Hydrogen/air Flamementioning
confidence: 99%